Difficulties Encountered by a Dyslexic Secondary School Student in Learning Science and Suggestions for Solutions - Hamiye Tırıl; Seda Okumuş (Journal of Science Learning, 2022)
This study aims to reveal the problems faced by a dyslexic student in learning science and determine what can be considered an effective science teaching method for this kind of learner. The case study design was used, and the study was conducted with a 7th-grade dyslexic female student. This study used observations and a semi-structured interview form as data collection tools. According to the findings, the problems faced by the student with dyslexia in learning science were generally compatible with the literature and immediately affected science learning. It was deduced that the student's reading skills, writing skills, motor skills, attention, memory and comprehension, language skills, use of sensory organs, and math skills are effective in learning science and that the development of these skills is necessary for understanding and comprehending science. In order to develop these skills, it is predicted that technology-based student-centered activities and individualized teaching may be beneficial, which is in line with the constructivist philosophy. In addition, it may be practical to give technology-supported reading extracts containing scientific texts, tasks involving social interaction, and writing tasks to improve students' reading, writing, and language skills.